Penerapan Latihan Batuk Efektif untuk Mengeluarkan Sputum pada Pasien Pneumonia Lobaris Superior Dextra - Utami, Maria Putri Sari; Taukhit, Taukhit; Mustafsiroh, Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the application of practical coughing exercises to expel sputum in nursing care for pneumonia patients. The research uses a case study method with evidence-based nursing, interviews, physical examination, observation, and document review. The study's results showed that after practical coughing exercises, the patient could expel retained sputum with a respiratory frequency of 20 x/minute and oxygen saturation of 100%. In conclusion, effective cough exercise therapy can positively affect pneumonia patients. Keywords: Effective cough, Pneumonia, Sputum